Stalinism reloaded : everyday life in Stalin-City, Hungary - Horváth, Sándor (2017)
Part 1. Identities – Myths – Downtown America – Urban villagers – Part 2. Relationships – Family – Abortion – Divorce – Part 3. Hierarchy – Bars – Hooligans – Slums – Prostitution